Antibiotic susceptibility of Fusobacterium necrophorum isolated from liver abscesses - K.F. Lechtenberg; Tiruvoor G. Nagaraja; M. M. Chengappa (Kansas Agricultural Experiment Station Research Reports, 1998)
Antibiotic susceptibility patterns of thirty-seven isolates of Fusobacterium necrophorum (21 biotype A and 16 biotype B) from liver abscesses of feedlot cattle were determined. These isolates were generally susceptible to penicillins, tetracyclines (chlortetracycline and oxytetracycline), lincosamides (clindamycin and lincomycin), and macrolides (tylosin and erythromycin) but resistant to aminoglycosides (kanamycin, neomycin, gentamycin and streptomycin), ionophores(except narasin), and peptides (avoparcin, polymixin, and thiopeptin). Differences in antibiotic sensitivity patterns were observed between the two biotypes only for clindamycin and lincomycin. The minimum inhibitory concentrations (MIC) of FDA-approved antibiotics for liver abscess control did not parallel their efficacy in preventing clinical liver abscesses in feedlot cattle. Continuous tylosin feeding did not appear to induce antibiotic resistance in F.necrophorum.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen' s Day; 1998; Beef; Fusobacterium necrophorum; Liver abscesses; Antibiotic susceptibility